2018
DOI: 10.1002/mrd.23084
|View full text |Cite
|
Sign up to set email alerts
|

Effective attenuation of glyphosate‐induced oxidative stress and granulosa cell apoptosis by vitamins C and E in caprines

Abstract: Pesticides are known to cause a wide range of reproductive problems that possess degenerative effects on mammalian fertility. Glyphosate (GLP), a broad‐spectrum organophosphate herbicide, is known to be a potent mammalian toxicant. The present study aims at assessing the GLP‐induced (0.1, 2.0, and 4.0 mg/ml) granulosa cells toxicity and evaluating the mitigating effects of vitamins C and E (0.5 mM and 1.0 mM) in healthy caprine antral follicles, cultured in vitro in a dose‐ and time‐dependent manner (24, 48, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Regarding the follicle population, in D. rerio, exposure to Roundup WG at 65 µg/L for 15 days led to an increased number of initial follicles and a decreased number of intermediate and tertiary follicles compared with the control group [41]. Similar results were found with Roundup Full II ® Argos in Friesian ewes exposed during the first day of life, with an increase in granulosa cell apoptosis [34].…”
Section: Ovarian Alterations In Vivo Studiessupporting
confidence: 59%
See 1 more Smart Citation
“…Regarding the follicle population, in D. rerio, exposure to Roundup WG at 65 µg/L for 15 days led to an increased number of initial follicles and a decreased number of intermediate and tertiary follicles compared with the control group [41]. Similar results were found with Roundup Full II ® Argos in Friesian ewes exposed during the first day of life, with an increase in granulosa cell apoptosis [34].…”
Section: Ovarian Alterations In Vivo Studiessupporting
confidence: 59%
“…Regarding ovarian cell proliferation and viability, Alarcon et al [34] showed decreased ovarian cell proliferation associated with more multiple-oocyte follicles in Friesian ewes exposed to a GBH. Other alterations in ovaries exposed to GBHs have been observed, such as atrophy, fat deposition, vasodilatation, and cell calcification [21]; concentric membrane formation [39,41]; vacuolization [33,41]; first estrus delay in rats [31]; fragmented nuclei; condensed chromatin [42]; and an increase in fibroblasts and MEC [22]. These results show that GBHs, which contain G and formulants, have more toxic effects on ovarian cells than G alone, no matter the type of GBH, the development stage and duration of exposure, and the species.…”
Section: Ovarian Alterations In Vivo Studiesmentioning
confidence: 99%
“…As oxidative stress‐mediated reproductive infertility induced by heavy metals like Cd 2+ and Pb 2+ is partially reversible, it can be cured by chelating agents and rehabilitation of individuals away from the heavy metal‐loaded environments. Therapeutic potentials of natural antioxidants like vitamin C‐rich lemon, [ 108 ] vitamin C and E, [ 6,123 ] N ‐acetyl‐ l ‐cysteine, [ 124 ] and so forth, are needed to be explored against heavy metal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2,3 ] Among a group of toxic chemicals, metals are ubiquitous environmental toxicants and pose a serious threat to the ecological system, and human and animal health. [ 4–6 ] Metals and metalloids that have a comparatively high atomic density (>5 g/cm 3 ) and high atomic weight are known as heavy metals. [ 7 ] Examples of heavy metals include lead (Pb), mercury (Hg), cadmium (Cd), nickel (Ni), zinc (Zn), chromium (Cr), copper (Cu), silver (Ag), iron (Fe), palladium (Pd), platinum (Pt), metalloid arsenic (As), and selenium (Se).…”
Section: Introductionmentioning
confidence: 99%
“…However, agricultural and industrial sectors are closely associated with the substantial use of a broad spectrum of chemicals, encompassing pesticides that are used extensively to enhance the productivity of both farm and forest areas, various chemicals used in the manufacturing of plastics, and heavy metals in the production of vehicles, electronics, paints, and other materials (Bhardwaj, Mittal, Saraf, & Kumari, 2018; Leblanc, 2004; Manfo et al, 2012). All these different activities are unfortunately associated with the release of numerous hazardous elements/substances in the environment, which are associated with toxicity of different body organs/systems including the reproductive system of the animals (Manfo et al, 2012; Bhardwaj & Saraf, 2014; Bhardwaj, Mittal, & Saraf, 2018). Heavy metals [eg, lead, cadmium (Cd), and mercury] have no known biological functions in the human body, and are therefore considered as “toxic heavy metals”.…”
Section: Introductionmentioning
confidence: 99%